2010
DOI: 10.1038/tpj.2010.10
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of irinotecan and 5-fluorouracil toxicity and response in patients with advanced colorectal cancer

Abstract: Irinotecan and 5-fluorouracil (5-FU) are used to treat metastatic colorectal cancer. Irinotecan's active metabolite is inactivated by UDP-glucuronosyltransferase 1A1 (UGT1A1), which is deficient in Gilbert's syndrome. Irinotecan and metabolites are transported by P-glycoprotein, encoded by ABCB1. 5-FU targets folate metabolism through inhibition of thymidylate synthase (TYMS). Methylenetetrahydrofolate reductase (MTHFR) generates active folate necessary for haematopoiesis. We retrospectively genotyped 140 Swed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
90
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(95 citation statements)
references
References 52 publications
3
90
0
2
Order By: Relevance
“…Association between UGT1A1*28 and neutropenia (UGT1A1*28/*28 versus UGT1A1*1/*1 or UGT1A1*1/*28) Relevant data for the comparison of the risk of neutropenia between UGT1A1*28/*28 patients and those with a UGT1A1*1/*1 or UGT1A1*1/*28 genotype were available in 15 included trials (3)(4)(5)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Considering the individual subgroup, there was no evidence of publication bias according to either Begg's test or Egger's test (Table 3).…”
Section: Study Characteristics and Methodologic Quality (Association mentioning
confidence: 99%
See 1 more Smart Citation
“…Association between UGT1A1*28 and neutropenia (UGT1A1*28/*28 versus UGT1A1*1/*1 or UGT1A1*1/*28) Relevant data for the comparison of the risk of neutropenia between UGT1A1*28/*28 patients and those with a UGT1A1*1/*1 or UGT1A1*1/*28 genotype were available in 15 included trials (3)(4)(5)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Considering the individual subgroup, there was no evidence of publication bias according to either Begg's test or Egger's test (Table 3).…”
Section: Study Characteristics and Methodologic Quality (Association mentioning
confidence: 99%
“…UGT1A1*28 has been shown to be associated with decreased SN-38 glucuronidation in humans (3)(4)(5)(6)(7)(8)(9)(10)(11). The association between the UGT1A1*28 genotype and irinotecan-induced neutropenia has been extensively studied (3)(4)(5)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Seven of these studies found that UGT1A1*28/*28 patients had an elevated risk of neutropenia compared with those carrying UGT1A1*1 allele(s) (refs.…”
mentioning
confidence: 99%
“…Previous studies have shown contradicting results with regard to the role of MTHFR in toxicity in relation to 5-FU chemotherapy (6,13,17,(33)(34)(35). The contradictory results may reflect that the MTHFR 677C>T and MTHFR 1298A>C SNPs were not combined according to phenotypic effects, differences in treatment regimens, and inadequate statistical analyses.…”
Section: Discussionmentioning
confidence: 95%
“…In East Asian populations, including the Japanese, the association between UGT1A1 * 28 and * 6 polymorphisms and irinotecan-induced toxicities was previously investigated (3,5,6). In colorectal cancer, irinotecan-induced grade 3/4 neutropenia occurs more frequently in patients with the homozygous UGT1A1 * (7)(8)(9). These findings were similar for Japanese patients (9,10) and individuals with low enzyme activity constitute ~10% of the Japanese population (10,11).…”
Section: Introductionmentioning
confidence: 99%